K connectivity algorithm based on flow network in wireless sensor networks - Jie HU; Jie ZHAN; Baoquan REN (物联网学报)
Wireless sensor networks(WSN) connectivity is an important way to ensure network fault tolerance.Conventional multi-routing algorithms often have common paths,which will lead to premature connectivity failure of the whole WSN due to node damage,communication link interruption and other faults.Aiming at the common path problem,a solution was proposed to generate multiple paths on the common path through node splitting to support fault tolerance of WSN and ensure that each sensor node has K disjoint shortest paths of bounded length to the sinks.The simulation results show that the algorithm can provide better fault tolerance and ensure network connectivity.